Effect of anionic salts in concentrate mixture on some blood and urine minerals, acid-base balance and feed intake of dry pregnant cows on grass silage based feeding with high calcium intake - Tauriainen, Susanna; Sankari,Satu; Syrjälä-Qvist, Liisa (Agricultural Research Centre of Finland, 1998)
Ummessaolevien lehmien kokeessa arvioitiin kationi-anionitasapainon vaikutusta säilörehuvaltaisella ruokinnalla, kun kalsiumin saanti oli runsasta (82 g Ca/pv). Kationi-anionitasapaino laskettiin [(Na+ + K+) - (Cl- + S2-)] mEq/kg kuiva-ainetta (ka). Se oli joko +410 tai +81 mEq/kg ka. Kalsiumlisä annettiin kalsiumkarbonaattina. Suoloina käytettiin magnesiumkloridia, ammoniumkloridia ja -sulfaattia. Lehmät saivat säilörehua (5,2 kg ka), heinää (0,8 kg ka) ja täysrehua (1,7 kg ka) neljä viikkoa ennen odotettua poikimista poikimispäivään saakka. Veri- ja virtsanäytteitä otettiin 4, 3, 2 ja 1 viikkoa ennen odotettua poikimista, poikimispäivänä sekä 1 vrk ja 1 viikko poikimisen jälkeen. Tulosten mukaan ummessaolevien lehmien kationi-anionitasapainoa on vaikea säätää negatiiviseksi, kun säilörehun kaliumpitoisuus ylittää 30 g/kg ka. +81 mEq/kg ka ei aiheuttanut muutoksia verestä ja virtsasta mitattuihin parametreihin. Ainoastaan kalsiumin eritys virtsaan lisääntyi ja virtsan pH vähentyi kationi-anionitasapainon ollessa +81 mEq/kg ka verrattuna positiivisempaan kationi-anionitasapainoon (+410 mEq/kg ka). Koeväkirehun maittavuus oli tyydyttävä, kun anionisten suolojen määrä oli 3 Eq päivässä. 26 %:lla kokeen lehmistä ilmeni poikimisvuorokautena hypomagnesia, vaikka magnesiumin saanti oli suomalaisten suositusten mukaista (17 g Mg/pv). Näin ollen suomalaista magnesiumsuositusta tulisi lisätä ainakin silloin, kun kalsiumin saanti perusrehuista on runsasta.

The objective was to study the effects of anionic salts in a concentrate mixture on some blood and urine minerals, acid-base balance and intake of Ayrshire cows fed a grass silage based diet. Eighteen nonlactating, pregnant Ayrshire cows were divided randomly into two groups according to their expected calving date. Dietary cation-anion balance (DCAB), calculated as milliequivalents [(Na+ + K+) - (Cl- + S2-)] of the two diets was +410 mEq/kg of dietary dry matter (DM) in the high DCAB group and +81 mEq/kg of the dietary DM in the low DCAB group, respectively. The DCAB was formulated using NH4Cl, (NH4)2SO4 and MgCl2 as anionic salts. Cows received grass silage (5.2 kg DM), hay (0.8 kg DM) and a concentrate mixture (1.7 kg DM) until calving. Both diets were supplemented with 100 g CaCO3 to achieve a high Ca intake (82 g Ca/d). Blood and urine samples were collected 4, 3, 2 and 1 week before the expected calving date, at calving, the day after calving and 1 week following calving. Current data indicated that it may be difficult to formulate a diet with a negative DCAB, if the K content of grass silage is over 30 g/kg DM. As a result, no increase in blood Ca2+ and a relatively high urinary pH were observed. Furthermore, it may advantageous to increase Mg intakes above current Finnish recommendations when dietary Ca concentrations are high, since 28% of experimental cows experienced hypomagnaesemia at parturition.
Keywords: Ko; kalsium; magnesium; lehmät; ruokinta; calcium; cation-anion balance; cows; magnesium; minerals; palatability